2023
DOI: 10.1136/bmjgh-2022-010781
|View full text |Cite
|
Sign up to set email alerts
|

Linkages between malaria and malnutrition in co-endemic regions of India

Abstract: IntroductionMalaria and malnutrition are key public health challenges in India. However, the relationship between them is poorly understood. Here, we aimed to elucidate the potential interactions between the two health conditions by identifying the areas of their spatial overlap.MethodsWe have analysed the district-wise undernutrition and malaria data of 638 districts of India across 28 states and 8 union territories. Data on malnutrition parameters viz. stunting, wasting, underweight and anaemia, sourced from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…2 Given that under-nutrition and malaria disease coexist in malaria endemic areas, our findings beg for a further investigation using a more robust study design with sufficient sample size. 44 Our findings imply that at present, most of the under-nutrition cases in the County are not related to malaria disease. The low malaria coverage reported in our study is inconsistent with the facility based records.…”
Section: Discussionmentioning
confidence: 55%
“…2 Given that under-nutrition and malaria disease coexist in malaria endemic areas, our findings beg for a further investigation using a more robust study design with sufficient sample size. 44 Our findings imply that at present, most of the under-nutrition cases in the County are not related to malaria disease. The low malaria coverage reported in our study is inconsistent with the facility based records.…”
Section: Discussionmentioning
confidence: 55%
“…Anemia has not been found associated with the frequency of malaria episodes, but it has been demonstrated to be signi cantly associated with malnutrition [12]. In contrast, other studies have shown that malnutrition and anemia are associated with a higher risk of Plasmodium infection and infectious episodes [13,14].…”
Section: Introductionmentioning
confidence: 97%
“…This complex association persists in an interwoven vicious cycle that coexists in sub-Saharan Africa [ 14 ]. The interaction association between undernutrition and reducing asymptomatic malaria endemicity remains inconclusive with inconsistent findings [ 15 19 ].…”
Section: Introductionmentioning
confidence: 99%